The Chilean TURF system- How is it performing in the case of the loco fishery? - González, Jorge Alberto (2006)
Chilean benthic fisheries involve thousands of artisanal fishers, about 50 target species (most significantly loco, Concholepas concholepas (Bruguière), and a coastline spanning 38 latitudinal degrees. An overfishing crisis led to a closure of the loco fishery (1989 1992), and to the   incorporation of territorial use rights in fisheries(TURFs) into fisheries legislation. Organizations of artisanal fishers are entitled to co-manage parcels of seabed with the state. We used old and new data on the loco fishery of Region IV (the cradle of the system) to investigate the performance of TURFs, which presently encompass 36% of the prime habitat that contributed close to 82% of historical yield. Abundance within TURFs and legal catch are stabilized, the fishery looks orderly, and perception of TURFs is generally positive. The system is dual, however, and at least half of the catch is illegal, originating from background areas outside the TURFs. Corrective action requires incentives that would eliminate the illegal catch, increase fishermen´s participation, and provide simple feedback decision rules driven by data and more flexibility allowing fishermen to experiment and diversify activities. Attention is needed to biological processes at scales that transcend the boundaries of locally managed TURFs and to values and priorities other than biological sustainability that may be of societal significance.